2019
DOI: 10.1371/journal.pone.0215735
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of postpartum depression within one year after birth in urban slums of Dhaka, Bangladesh

Abstract: Postpartum depression (PPD) is a serious pubic health concern and known to have the adverse effects on mother’s perinatal wellbeing; and child’s physical and cognitive development. There were limited literatures on PPD in Bangladesh, especially in urban slum context. The aim of this study was to assess the burden and risk factors of PPD among the urban slum women. A cross-sectional study was conducted between November-December 2017 in three urban slums on 376 women within first 12 months of postpartum. A valid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
50
5
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 55 publications
17
50
5
8
Order By: Relevance
“…An unplanned pregnancy may also lead to economic burden and social judgment on the women which may be responsible for postnatal depression. This finding is consistent with the study done in South West Ethiopia [31], Bangladesh [34], public hospitals of Addis Ababa [28] and Benchi Maji Zone, Ethiopia [29]. In this study, mothers who gave birth for the first time were more likely to develop postnatal depression than those who gave birth more than four times This finding is consistent with a study done in Vietnam [32] and contradict with study done in Udupi Taluk, India [27].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…An unplanned pregnancy may also lead to economic burden and social judgment on the women which may be responsible for postnatal depression. This finding is consistent with the study done in South West Ethiopia [31], Bangladesh [34], public hospitals of Addis Ababa [28] and Benchi Maji Zone, Ethiopia [29]. In this study, mothers who gave birth for the first time were more likely to develop postnatal depression than those who gave birth more than four times This finding is consistent with a study done in Vietnam [32] and contradict with study done in Udupi Taluk, India [27].…”
Section: Discussionsupporting
confidence: 93%
“…This level of postnatal depression is almost similar with study done in Udupi Taluk, India (21.5%) [27], public hospitals of Addis Ababa (23.3%) [28], Benchi Maji Zone, Ethiopia (22.4%) [29] and Kenya (18.7%) [30]. However; it is lower than a study done in Southwest Ethiopia (33.82%) [31], Vietnam (27.6%) [32], China (30%) [33] and Bangladesh (39.4%) [34]. On the other hand, the level of postnatal depression in this study is higher than study done in Netaji Subhash medical college, India (12.8%) [35], Ghana (7%) [36], Sudan (9.2%) [37] and Eastern province capital of Saudi Arabia (17.8%) [38].…”
Section: Discussionmentioning
confidence: 99%
“…A higher prevalence of depressive symptoms was found in our study to be supported by a recent community-based urban study in the country [34] and in other developing contexts, e.g., a rural study in Nigeria [40]. Higher numbers of child marriages, higher rates of girls' dropout from high school despite GoB initiatives, little knowledge of the childcare of these mothers, increasing trends of nuclear families, and women's participation in economic activities resulting in reduced time for child care might have negative impacts on a mothers' higher mental stress, resulting in depression.…”
Section: Discussionsupporting
confidence: 91%
“…The slightly higher prevalence of depressive symptoms in our study could be due to participation of relatively poorer mothers in the study. A recent population-based study in three urban slums of Dhaka city, Bangladesh found a prevalence of 39.4% using the Edinburgh Postnatal Depression Scale (EPDS) among mothers within 12 months following delivery [34] and 46.2% in another urban settings using SRQ-20 [35]. In the South Asian context, the prevalence of depression varied in different countries.…”
Section: Discussionmentioning
confidence: 99%
“…Mental health problems represent 5.6% of the total studies. Depression in particular has been studied regularly (e.g., [74]), often in connection with abortion (e.g., [75]). Non-specific studies were mentioned 106 times, with most of the studies also being conducted on the city level (50%).…”
Section: Analysis By Health Categoriesmentioning
confidence: 99%